Physicochemical, microbiological and toxicological quality of raw milk in cattle basins of the region Puno-Peru - Brousett-Minaya, Magaly (2015)
The objective of this study was to evaluate the quality of raw milk in seven representative basins of the region Puno. The results were compared with the standards established by the International Standard for milk and milk products NTP 200.001-2003 and the Official Mexican Standard NOM-155-SCFI-2012 for the parameters of protein and lactose in the absence of Peruvian parameters. For physicochemical characterization pH, acidity, density, fat, protein, lactose, total solids, fat solids was determined microbiological analysis of E. coli and mesophilic, just as we also performed the study spanned pesticide residue analysis such as organochlorines, organophosphates, carbamates and pyrethroids with sensitivity 1.0ug/g sample which gave negative results for the four groups of pesticides, the physicochemical determinations over 50% of the basins (except for pH and acidity) is found within the standards of the NTP and NOM. The presence of mesophilic were mostly found within the parameters except for two milksheds and as for E. Coli any basin met established standards found one poor quality milk hygienic.